Alterações bioquímicas, fisiológicas e ultraestruturais em sementes e plantas de tomate expostas ao chumbo - Moraes, Caroline Leivas (2011)
Lead (Pb) is a potentially toxic metal, it can be added to soils via phosphate fertilizers, industrial waste and sewage sludge. Therefore, the purpose of this research was to evaluate the changes induced by different concentrations of lead acetate in physiological characteristics, biochemical and ultrastructural of seeds and tomato plants. The experiment was divided into two trials, where the first evaluated the effect of metal on the physiological potential of seeds and initial seedling growth, chlorophyll, carotenoids and ultrastructural alterations. In the first trial tomato seeds were exposed to different concentrations of lead acetate (zero; 0,25; 0,5 and 0,75mM). In the second trial, plants grown for 30 days in a greenhouse were transplanted to plastic pots and kept in climate-controlled growth room. After a period of 14 days, there were four applications of different concentrations of lead acetate, which were irrigated with nutrient solution. Four evaluations of gas exchange and chlorophyll a fluorescence were determined, and at the end of the experiment, there were measured the activity of the enzymes superoxide dismutase, catalase, ascorbate peroxidase, glutathione reductase, lipid peroxidation and H2O2 content, as well as the growth characteristics. Results demonstrated that lead acetate reduced the seed viability and caused a reduction in growth characteristics, and distortions in the thylakoids of chloroplasts and the amount and size of starch grains. The content of chlorophyll a, b and carotenoids were dramatically affected by lead acetate. In CO2 assimilation, stomatal conductance and transpiration, there was a significant decrease for all variables, as well as on growth characteristics, and the root system was more sensitive to the metal. Regarding the antioxidant enzyme system in general, there was an increased activity of the enzymes analyzed, but not enough to prevent lipid peroxidation of membranes. In conclusion, lead acetate reduces the physiological quality of tomato seeds. In plants, it has direct effects on the biochemical phase of photosynthesis by inducing stomatal closure, reducing considerably the input of CO2 into the interior mesophyll.